IMPACT FOREIGN DEBT AND FOREIGN INVESTMENT TO ECONOMIC GROWTH AND LEVEL POVERTY IN ASEAN COUNTRY - B2051142002, EKO SUPRIYANTO (Jurnal Ekonomi Daerah (JEDA), 2016)
Foreign debt and foreign direct investment fund to increase economic development so as to impact economic growth and pressing poverty ASEAN countries. This research use descriptive methods, to see the influence of the foreign debt and foreign direct investment againt economic growth and influence of foreign debt and foreign direct investment against poverty levels as well as the influence of economic growth the poverty level of the ASEAN countries. Testing research of linier regression models using, as well as statistical analysis tool that is the determation foefficient and t-test. The results of the analysis show the foreign debt and foreign direct investment significan influential toward growth economic and level of poverty, while the influential economic growth but not significantly to poverty level in 8 countries of ASEAN in the period 2005-2014 Keyword : Foreign debt, Foreign Direct Investment, Economic Growth, Poverty